2000
DOI: 10.2337/diabetes.49.11.1794
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of p38 mitogen-activated protein kinase alpha and beta by insulin and contraction in rat skeletal muscle: potential role in the stimulation of glucose transport.

Abstract: The stress-activated p38 mitogen-activated protein kinase (MAPK) was recently shown to be activated by insulin in muscle and adipose cells in culture. Here, we explore whether such stimulation is observed in rat skeletal muscle and whether muscle contraction can also affect the enzyme. Insulin injection (2 U over 3.5 min) resulted in increases in p38 MAPK phosphorylation measured in soleus (3.2-fold) and quadriceps (2.2-fold) muscles. Increased phosphorylation (3.5-fold) of an endogenous substrate of p38 MAPK,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
147
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(159 citation statements)
references
References 46 publications
11
147
0
1
Order By: Relevance
“…This is comparable to what has been observed after p38 MAPK inhibition with SB-203580 in 3T3-L1, L6 muscle cells, and isolated soleus muscle (36,40). Furthermore, inhibition of the enzyme with a dominant negative mutant of p38 MAPK also diminished the insulin-stimulated glucose uptake by 40% (34).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This is comparable to what has been observed after p38 MAPK inhibition with SB-203580 in 3T3-L1, L6 muscle cells, and isolated soleus muscle (36,40). Furthermore, inhibition of the enzyme with a dominant negative mutant of p38 MAPK also diminished the insulin-stimulated glucose uptake by 40% (34).…”
Section: Discussionsupporting
confidence: 69%
“…Recent studies have suggested that p38 MAPK is a key signaling intermediate in the regulation of glucose transport by insulin (34,36,40). We therefore determined whether vanadate regulates this enzyme in cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fact that insulin did not alter plasma membrane GLUT1 levels makes it difficult to reconcile how this transporter isoform could fully account for this discrepancy. In the same context, there is also significant evidence that insulin and other stimuli can alter the activity of GLUT4 transporters (61,62). Thus, the ability of insulin to stimulate the "intrinsic activity" of the basal pool of GLUT4 in the plasma membrane may not be dependent on cortical F-actin.…”
Section: Discussionmentioning
confidence: 89%
“…Insulin per se activates p38 MAPK in the VSMC 29 and other cell types. [30][31][32] This suggests that interactions between hyperglycemia, insulin levels, and the p38 pathway activity may be more complex. This issue is even more relevant with respect to the fact that previous experimental in vivo studies were performed in diabetic animals without insulin treatment.…”
Section: Renal P38 In Experimental Diabetesmentioning
confidence: 99%